Study on Ability of Elementary School Teacher in Writing Test Items During The Pandemic Time of Covid-19 - Wuryanti, Sri; Muhardis, NFN (Indonesian Journal of Educational Assessment, 2020)
The purpose of this study was to obtain information about the ability of elementary school teachers in composing test questions in private universities. This research uses qualitative research, which describes empirical reality using a descriptive approach. This study also uses a literature study, with documents to find some field data that occurs in the form of questions on several subjects. Meanwhile, the descriptive method is finding facts with the right interpretation, namely understanding the concept of the material, the ability to use the rules of the question. Meanwhile, the data analysis used was (1) the subject matter expert's judgment in interpreting some of the item test document findings, (2) theoretically and empirically the item had met the standard question rules. This research was found, during the COVID 19 pandemic, all parents or guardians have a 100% chance of assisting with distance learning as unprecedented. The sample consisted of nine subject teachers and the population was all fourth-grade teachers in primary schools as research subjects. So the assessment also uses offline and online so that it is found, (1) biased test questions, because the linguistic structure of the main sentence and explanatory sentences, is wrong in choosing questions with answers, (2) does not understand the rules about the questions: such as homogeneity of questioners, long and short answers, the use of standard Indonesian. Meanwhile, some of the test questions that were found to have problems were Indonesian, Natural Science, Character, and Boy Scouts. From 12 items, 4 items had material concept errors and 8 items error in the rules.